The mechanics of the retina: Müller glia role on retinal extracellular matrix and modelling - Prieto-López, Laura; Pereiro, Xandra; Vecino, Elena (Frontiers in Medicine, 2024)
The retina is a highly heterogeneous tissue, both cell-wise but also regarding its extracellular matrix (ECM). The stiffness of the ECM is pivotal in retinal development and maturation and has also been associated with the onset and/or progression of numerous retinal pathologies, such as glaucoma, proliferative vitreoretinopathy (PVR), age-related macular degeneration (AMD), epiretinal membrane (ERM) formation or uveitis. Nonetheless, much remains unknown about the biomechanical milieu of the retina, and specifically the role that Müller glia play as principal mechanosensors and major producers of ECM constituents. So far, new approaches need to be developed to further the knowledge in the field of retinal mechanobiology for ECM-target applications to arise. In this review, we focus on the involvement of Müller glia in shaping and altering the retinal ECM under both physiological and pathological conditions and look into various biomaterial options to more accurately replicate the impact of matrix stiffness in vitro.